Relationships The Role of Farm Group with Rice Farmer Social Status in Cialam Jaya Village Konda Sub District South Konawe District - Batoa, Hartina; Salahuddin, Salahuddin; Hamzah, Awaluddin; Purwanti, Rahayu Endah; Iskandar, Andi Dheviani Oksaputri (Buletin Penelitian Sosial Ekonomi Pertanian Fakultas Pertanian Universitas Haluoleo, 2020)
This study aims to determine the relationship between the role of farmer groups and the social status of lowland rice farmers in Cialam Jaya Village, Konda Sub District, South Konawe District. This research was conducted in Cialam Jaya Village in September-December 2019. The determination of the research area was carried out purposively with the consideration that Cialam Jaya Village is one of the centres for lowland rice production and has farmer groups. Simple random sampling (simple random sampling) takes 10% or as many as 26 respondents of rice farmers. The data analysis used was the Spearman Rank Correlation analysis. The results showed that the role of the group was significantly related to the socioeconomic status of lowland rice farmers, with a significance value of 0.019.